Analysis of the Mechanism of Action of Atractylodes macrocephala Koidz Polysaccharide on Breast Cancer-Related Depression Based on the TLR4/MyD88/ NF-κB Signaling Pathway - Li, Xuefei; Fu, Cong; Tang, Shanshan; Yang, Jian; Shi, Xiaonan; Cui, Shanshan (Indian Journal of Pharmaceutical Education and Research, 2025)
Objectives: In the study, we analyzed the effect of Atractylodes macrocephala Koidz Polysaccharide (AMKP) on Breast Cancer-Related Depression (BCRD) to provide new references for future treatment of BCRD. Materials and Methods: First, after the liver toxicity test to determine the concentration of AMKP, we established a mouse model of BCRD and divided it into model, fluoxetine and AMKP groups treated with saline, fluoxetine and AMKP gavage, respectively. In addition, a group of normal control mice was set up. We subjected mice to the tail suspension test, forced swimming test and sugar water preference test. After completion, the mice were executed and blood and brain tissues were collected to detect inflammatory factors, immune cells and neurotransmitters by Enzyme Linked Immunosorbent Assay (ELISA), flow-through cell counting and chromatography. Finally, Western blot was performed to detect the changes of TLR4/MyD88/NF-κB signaling pathway in the brain tissues of mice in each group BCRD. Results: Compared with the model group, mice in the AMKP and fluoxetine groups had a lower rate of sugar-water consumption, while the resting time in the tail-suspension test and forced-swimming test was prolonged (p<0.05). In addition, although the neurotransmitter and synaptic functions of the AMKP group were not as excellent as those of the fluoxetine group, the AMKP group had lower inflammatory factors and better immune functions (p<0.05). Conclusion: AMKP improves neurological function and depressive behavior in BCRD mice by inhibiting the TLR4/MyD88/NF-κB pathway.
Keywords: Atractylodes macrocephala Koidz Polysaccharide; Breast cancer-related depression; Immune function; Neurological function; TLR4/MyD88/NF-κB